Ants act as olfactory bio-detectors of tumours in patient-derived xenograft mice. Issue 1991 (25th January 2023) - Piqueret, Baptiste; Montaudon, Élodie; Devienne, Paul; Leroy, Chloé; Marangoni, Elisabetta; Sandoz, Jean-Christophe; d'Ettorre, Patrizia
Abstract : Early detection of cancer is critical in medical sciences, as the sooner a cancer is diagnosed, the higher are the chances of recovery. Tumour cells are characterized by specific volatile organic compounds (VOCs) that can be used as cancer biomarkers. Through olfactory associative learning, animals can be trained to detect these VOCs. Insects such as ants have a refined sense of smell, and can be easily and rapidly trained with olfactory conditioning. Using urine from patient-derived xenograft mice as stimulus, we demonstrate that individual ants can learn to discriminate the odour of healthy mice from that of tumour-bearing mice and do so after only three conditioning trials. After training, they spend approximately 20% more time in the vicinity of the learned odour than beside the other stimulus. Chemical analyses confirmed that the presence of the tumour changed the urine odour, supporting the behavioural results. Our study demonstrates that ants reliably detect tumour cues in mice urine and have the potential to act as efficient and inexpensive cancer bio-detectors.